Liver dysfunction associated with dengue virus infection: state of the art. Systematic Review - Chele-Choez , Víctor Emilio; Lalvay-Arpi, Julissa Mishel; Alcocer-Díaz, Sirley (Kasmera, 2021)
Liver dysfunction is the decrease in liver functions, which limits the fulfillment of its main functions such as the elimination of harmful substances from the bloodstream, digestion of food and synthesis of vitamins. When this organ is affected by viruses such as dengue, it can cause enzymatic alterations, inflammation, more serious deficiencies such as acute liver failure. The objective of the research was to describe the association between liver dysfunction and dengue virus infection. A descriptive research with documentary design was carried out, through a systematic review in the electronic databases Pubmed, SciELO, Elsevier and Google Scholar, including articles published in the last four years in English - Spanish languages. Hepatic dysfunction presents in the form of transaminitis with around 65-97% in the cases of patients with dengue. Serious alterations and cases with the presence of acute liver failure due to dengue have been described. Post-mortem studies have revealed viral particles in liver tissue. Based on the analysis of the studies, it is suggested that dengue infection affects tissues and organs, including liver tissue, however, the mechanism of action by which the virus induces damage to liver tissue is not yet well defined